PEMBERDAYAAN KWT BINA LESTARI MELALUI OPTIMALISASI PRODUKSI, PEMASARAN, DAN KEUANGAN UNTUK MENINGKATKAN DAYA SAING USAHA - Siti Maesaroh; Ratna Suryani; Walid Rudianti (Perwira Journal of Community Development, 2026)
This community service program was carried out to empower the Bina Lestari Women Farmers Group (KWT) in Bojanegara Village, Banjarnegara. The objective of the program was to enhance the production, marketing, and financial record-keeping of the cassava cracker (opak singkong) business to improve its competitiveness and sustainability. The main challenges faced by the partner included limited production equipment, traditional marketing practices with restricted market reach, and irregular financial records. The implementation method consisted of socialization, training, technology adoption, mentoring, and evaluation. The community service team provided molding and drying machines for opak production, delivered digital marketing training accompanied by website development, and assisted members in preparing simple financial reports. The results demonstrated significant improvements, including a 20% increase in sales turnover compared to previous conditions. Cassava cracker production became more efficient and consistent, marketing expanded through digital platforms, and financial documentation became more organized. Furthermore, the adoption of appropriate technology and continuous mentoring increased members’ skills, independence, and confidence in managing their business.